Role of adsorption and oxidation in porous carbon aerogel/persulfate system for non-radical degradation of organic contaminant. (February 2020) - Jiang, Lili; Wang, Qi; Zhou, Minghua; Liang, Liang; Li, Kerui; Yang, Weilu; Lu, Xiaoye; Zhang, Ying
Abstract: A porous carbon aerogel (CA) was prepared to activate persulfate (PS) for the removal of phenol. The adsorption of phenol on CA and its removal in CA/PS system was fitted to a second-order model and first-order kinetic model, respectively. Influencing factors of CA/PS such as pH, CA dose, PS concentration, phenol concentration and temperature were investigated. CA/PS presented good performance on phenol removal over a pH range of 3–11 with the highest removal obtained at pH 7. Four kinds of organic pollutants including tetracycline, Rhodamine B, Safranine T and malachite green were investigated in the CA/PS system, proving that the adsorption of the contaminants benefitted their subsequent oxidation removal. The removal of aromatic compounds (phenol, p -diphenol, p -chlorophenol, and p -nitrophenol) in CA/PS system followed a decreasing order of hydroxyl > chlorine > nitro. The radical scavenging experiments suggested the removal of phenol was mainly through a non-radical pathway. The study presented the preparation and application of a green catalyst to activate PS, which is very promising for the development of the technology and the treatment of phenolic wastewater. Highlights: The adsorption and oxidation process in CA/PS system were investigated separately. The adsorption of contaminants benefitted their subsequent oxidation removal. The removal of four aromatic compounds followed an order of hydroxyl > chlorine > nitro. Phenol removal by PS activated with CA was through a non-radical pathway.